The use of biofeedback training techniques for improving heart rate variability scores and achievements in science subjects among primary school students - Hasmiza, Yaakob; Muhammad Nubli, Abdul Wahab; Abdul Rashid, Abdul Aziz; Ibrahim, Is’haq; Mohd Ropizam, Mohamad Zainun (Human Resource Management Academic Research Society (HRMARS), 2023)
Biofeedback training techniques can help to improve students’ achievement levels in a subject. Accordingly, this study investigates differences in HRV scores between high- and low-performing students. This quasi-experimental quantitative study involved conducting pre- and post-tests on students who received biofeedback training during their science-learning integration process. The results show that students with good performance had better coherence scores compared to the poor performers. This is due to the regulation of the sympathetic and parasympathetic nervous systems among them. However, following biofeedback training, it was found that the higher HRV scores of the poor performing students exceeded that of the good performing students. This shows that they can compete with good performing students provided they receive more specific guidance. The findings of the study show that the HRV biofeedback training technique is suitable for use in helping rural primary school students improve their achievement in science and other subjects which require more effective alignment of learning techniques.